LOAD TRANSFER ANALYSIS IN BONDED-BOLTED HYBRID JOINTS - CHEN XiangMing; CHAI YaNan; YUAN Fei; YU Fei; CAO Su (Jixie qiangdu)
A finite element method of the hybrid（ bonded/bolted） joints is developed,and load transfer is analyzed. The three-dimensional cohesive zone model is used to simulate adhesive layer. Elasto-plastic deformation of metal structure is taken into account. Meanwhile,experimental data of the bonded joints,the bolted joints and the bonded/bolted hybrid joints are obtained and compared with the predictions. A good agreement between experimental results and numerical predictions is observed. In addition,single bolt and double bolts hybrid（ bonded/bolted） joints models are developed,and analysis shows that load-bearing capacity of single bolt hybrid isn’t improved,relative to bonded joint. Meanwhile,in the double bolts hybrid joints,adhesive layer outside of the bolts is destroyed soon,because of biggish peeling force. That inside of bolts is carried pure shear force due to normal constraint force of bolts,and it could enhance carrying capacity of the adhesive layer. So the parameters and forms of bonded-bolted hybrid joints are improved,as enhanced the joints strength.